Inovasi Pembelajaran Pendidikan Pancasila Di Sekolah Dasar: Model Pelita Sebagai Pendekatan Efektif - Anida Safitri; Ahmad Suriansyah; Ratna Purwanti (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
The problem addressed in this study is the monotonous and unvaried learning process, the lack of student engagement, and the absence of attractive learning models and media, which causes students to become easily bored. This research aims to address the low levels of teacher and student activity, as well as students' critical thinking and collaboration skills in the subject of Pancasila Education by implementing the PELITA learning model. The study was conducted as a Classroom Action Research (PTK) over four sessions with fourth-grade students at SDN Kota Raja. Data were collected using both qualitative and quantitative approaches. The results showed significant improvements in teacher and student activity, critical thinking skills, collaboration, and student learning outcomes. The PELITA model proved effective and is recommended as an innovative learning alternative to enhance the quality of education.